LITHOFACIES STUDY OF BIMA SANDSTONE IN GURIN AND ITS ENVIRONS, YOLA SUB-BASIN, NORTHERN BENUE TROUGH, NIGERIA - Margimari, Useiju James; Mamman, Yusuf Dabari; Valdon, Yunis Boga; Adeniyi, Amodu (FUDMA Journal of Sciences, 2026)
Understanding the distribution of various lithological units, along with the environmental conditions and depositional settings, is essential for building a geological understanding of an area. This study focuses on the lithofacies in Gurin and its environs to enhance geological and paleoenvironmental understanding. The study involved field mapping and laboratory analysis. The mapping involved the identification of rocks, their lithological contacts and sampling while petrographic analysis was performed on the fifteen (15) representative sampled rocks. The rocks in the area are predominantly composed of sandstone and a few volcanic plugs. The study identified five (5) lithofacies within the Bima sandstone: trough cross-bedded sandstone (St), planar cross-bedded sandstone (Sp), ripple cross-laminated sandstone (Sr), parallel laminated sandstone (Sh), and mudstone facies (Fm) in which the planar cross-bedded (Sp) dominated the area. These lithofacies indicate a fluvial depositional setting, specifically a braided river environment, based on the fining upward sequence and primary structures identified. Petrographic analysis revealed that the Bima sandstone is predominantly composed of quartz (70-99%), with minor amounts of feldspars (1-28%) and rock fragments (1-5%). Based on their composition, the sandstones are predominantly quartz arenite with minor subarkosic and arkosic sandstone. Petrographic studies show that the sandstone is predominantly composed of monocrystalline quartz grains with intercrystalline boundaries; the abundance of monocrystalline quartz grains with intercrystalline boundaries suggests derivation from plutonic source rocks. This study provides valuable insights into the lithofacies, depositional environments, and petrographic characteristics of the Bima Sandstone, contributing to the geological understanding of the area.